A discursive analysis of the narratives emerging from coverage of rape in South African newspapers - Ferreira, Kate (My University, 2016)
Rape is a predominant crime and a social issue in South Africa today. South Africa’s incidence of rape is among the highest in the world. Identifying and understanding the dominant rape narratives in news media is useful in pinpointing how the media represents the crime of rape. It is understood through agenda-setting theory that news media plays an important role in how topics come onto the national agenda, giving news media a particular influence in society. Further, through discourse analysis and narrative theories, research has shown how what people read and hear can influence their understanding of those matters, and can drive social change or maintain the stability of social structures. Some theorists take this further, arguing that narrative fundamentally informs how humans make sense of the world, that reality is discursively constructed. The research below attempts to access, reveal and unpack these dominant narratives as they pertain to rape, using a combination of corpusbased analysis and critical discourse analysis techniques on two corpora of South African newspaper text from the first quarter of 2013, and tied to a specific case study, the rape and murder of Anene Booysen. The resultant findings also provide a snapshot of the dominant ideology and social practices in South Africa over the time period studied, as discourse and narrative are implicitly tied to power in society
Research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Art (Journalism and Media Studies), Johannesburg, 2016
Keywords: Discourse analysis, Narrative--Social aspects; Rape--Press coverage--South Africa; Rape in mass media; Journalism--South Africa